STUDENTSâ DIFFERENCES AND THEIR OUTCOMES IN ENGLISH LEARNING - Fadillah, Ridha (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2015)
This paper aims to investigate the studentsâ differences and studentsâ outcomes in English learning at State Vocational High School 3 (SMKN 3) Purwokerto, Central Java. The samples were second graders at that school. They were 177 fifteen to nineteen year old students. The results indicated that the studentsâ both English learning motivation and English language anxiety were at moderate level. There was significant negative relationship between motivation and outcome, but positive correlation between studentsâ anxiety and outcome was indicated. It showed that although the studentsâ anxiety was high, their learning outcome was till good.